2014
DOI: 10.1038/lsa.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

Tweezing and manipulating micro- and nanoparticles by optical nonlinear endoscopy

Abstract: The precise control and manipulation of micro-and nanoparticles using an optical endoscope are potentially important in biomedical studies, bedside diagnosis and treatment in an aquatic internal organ environment, but they have not yet been achieved. Here, for the first time, we demonstrate optical nonlinear endoscopic tweezers (ONETs) for directly controlling and manipulating aquatic micro-and nanobeads as well as gold nanorods. It is found that two-photon absorption can enhance the trapping force on fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…Our observation confirms that this process is convective flow assisted; (2) Although the heat was dissipating during the 2 s laser scanning, the convective flow is still enough to attract more GNRs to the center; (3) The trapping process can be quantified by the average intensities over time as shown in figure 2(D) (excluding the big clusters due to the fact particles were aggregated before entering the FOV). A rapid increase of intensity over time implies a positive feedback loop as described earlier by Gu et al [22]. Trapping with less frequent laser scanning, i.e.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Our observation confirms that this process is convective flow assisted; (2) Although the heat was dissipating during the 2 s laser scanning, the convective flow is still enough to attract more GNRs to the center; (3) The trapping process can be quantified by the average intensities over time as shown in figure 2(D) (excluding the big clusters due to the fact particles were aggregated before entering the FOV). A rapid increase of intensity over time implies a positive feedback loop as described earlier by Gu et al [22]. Trapping with less frequent laser scanning, i.e.…”
Section: Resultsmentioning
confidence: 88%
“…When more heat is generated with accumulation of GNRs at the focus, the trapping range is extended due to the convective flow (figure 1(B)). It has been reported that this effect was observable as the concentration increases to 10 3 per nanoliter [22]. In following measurements, we used the stock concentration of GNR, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…2a)63334. To maximize the excitation efficiency, a pair of gratings is used as pre-chirp unit in the dispersion compensation module (DCM) (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…By exploiting the optical-trapping effect, [116][117][118][119][120][121][122] FsLDW also enables the direct assembly of metallic nanoparticles into desired microstructures through the "femtosecond-laser photodynamic assembly (FsL-PDA)" process (depicted in Figure 1c). Using metal nanoparticles as nano-building-blocks, Sun and co-workers first achieved the FsL-PDA of metallic microstructures.…”
Section: Femtosecond-laser Photodynamic Assembly Of Metal Nanoparticlesmentioning
confidence: 99%